Awareness of pro-tobacco advertising and promotion and beliefs about tobacco use: Findings from the Tobacco Control Policy (TCP) India Pilot Survey - Maansi Bansal-Travers; Geoffrey T. Fong; Anne C.K. Quah; Genevieve Sansone; Mangesh S. Pednekar; Prakash C. Gupta; Dhirendra N. Sinha (Springer, 2019)
Tobacco companies are utilizing similar strategies to advertise and promote their products in developing countries as they have used successfully for over 50 years in developed countries. The present study describes how adult smokers, smokeless tobacco users, and non-users of tobacco from the Tobacco Control Project (TCP) India Pilot Survey, conducted in 2006, responded to questions regarding their perceptions and observations of pro-tobacco advertising and promotion and beliefs about tobacco use. Analyses found that 74% (n = 562) of respondents reported seeing some form of pro-tobacco advertising in the last six months, with no differences observed between smokers (74%), smokeless tobacco users (74%), and nonsmokers (73%). More than half of respondents reported seeing pro-tobacco advertising on store windows or inside shops. Overall, this study found that a significant percentage of tobacco users and non-users in India report seeing some form of pro-tobacco advertising and promotion messages. Additional analyses found that smokers were more likely to perceive tobacco use as harmful to their health compared with smokeless tobacco users and non-users (p < 0.01). The findings from this study reiterate the need for stronger legislation and strict enforcement of bans on direct and indirect advertising and promotion of tobacco products in India.